Pandemic Hinders First-Time Voter Engagement in Indonesia: Pandemi Menghambat Keterlibatan Pemilih Pemula di Indonesia - Asri Yuni Lestari; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the role of the General Election Commission (KPU) in boosting first-time voter participation in Seketi Village, Balongbendo District, Sidoarjo. Using qualitative methods, data were collected via interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The KPU's roles as Regulator and Dynamistator were effectively implemented, but their roles as Catalyst and Facilitator were less successful. Socialization efforts and provided facilities were hindered by the pandemic and low engagement from first-time voters, leading to decreased voter participation. The findings highlight the need for improved communication strategies and resource utilization to enhance first-time voter engagement. Highlights: Effective Roles: KPU succeeded as Regulator and Dynamistator. Pandemic Impact: Socialization and voter engagement hindered by COVID-19. Communication Gaps: Insufficient social media use reduced first-time voter information. Keywords: General Election Commission, first-time voters, voter participation, regional elections, qualitative study